2019
DOI: 10.3390/medicina55060287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hematological Parameters in Predicting Fuhrman Grade and Tumor Stage in Renal Cell Carcinoma Patients Undergoing Nephrectomy

Abstract: Background and objective: We investigated the ability of preoperative serum values of red blood cell distribution width (RDW), neutrophil lymphocyte ratio (NLR) and plateletcrit (PCT) to predict Fuhrman grades (FG) and tumor stages of renal cell carcinoma in patients who underwent radical nephrectomy. Materials and methods: Records of 283 patients that underwent radical or partial nephrectomy of renal masses at our clinic between January 2010 and April 2018, whose pathology results indicated renal cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
2
1
Order By: Relevance
“…In the study performed by Widz et al, high NLR (≥2,69) significantly correlated with worse survival outcome and higher tumor stage (26). Kısa et al reported that higher NLR (>2,6) was associated with increased risk of pT 3-4 tumors (27). In our study, a cut-off value of 2,31 was associated with increased risk of tumors > 4 cm and it was compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…In the study performed by Widz et al, high NLR (≥2,69) significantly correlated with worse survival outcome and higher tumor stage (26). Kısa et al reported that higher NLR (>2,6) was associated with increased risk of pT 3-4 tumors (27). In our study, a cut-off value of 2,31 was associated with increased risk of tumors > 4 cm and it was compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…In ROC curve analysis, a larger AUC indicates a better diagnostic efficiency. Kisa E et al found that PCT had a significant association with a high stage of RCC, whereas it was not associated with a high grade of tumor (23). Concordantly, when we used ROC curves to analyze the performance of PCT and NLR for distinguishing higher stage and grade of tumor, we found that high PCT was significantly associated with high stage and grade.…”
Section: Discussionsupporting
confidence: 60%
“…We also conclude that there is not a significant linear correlation between NLR levels with Fuhrman grade and recurrence rate in our study population. These findings are different from those of the previous study, mostly suggesting that the elevation of NLR will also increase the Fuhrman grade and vice versa [28,29]. For recurrence rate, previous studies found that high NLR was correlated with a high tendency of recurrence rate [30,31].…”
Section: Discussioncontrasting
confidence: 56%